PENGARUH EMOTIONAL INTELLIGENCE TERHADAP KESIAPAN KERJA MAHASISWA PENDIDIKAN TEKNIK BANGUNAN UNIVERSITAS PENDIDIKAN INDONESIA - Jajang Nurjaman; Dedy Suryadi; Sri Rahayu (Universitas Pendidikan Indonesia (UPI), 2023)
Society 5.0 is a challenge for the Indonesian people. These challenges are the cause of increasingly stringent entry into the world of work. Competition to enter the world of work which is increasingly stringent, has increased the number of unemployed in Indonesia. The unemployment rate which has increased, apart from being caused by the low competence knowledge possessed, is due to the lack of readiness for student work. Work readiness is a condition in which individuals are mentally and physically ready to carry out work-related activities. One of the factors that influences work readiness is emotional intelligence. A person with high emotional intelligence, has the ability to control himself, has the endurance to face obstacles, lacks self-satisfaction, can regulate moods, empathizes and can control his emotions so that he is able to control the anxiety that is within so as not to interfere with the ability to think. This study aims to find out the description of emotional intelligence and work readiness of students, as well as how emotional intelligence influences the work readiness of Building Engineering Education students Universitas Pendidikan Indonesia. The research method used is associative descriptive research with a quantitative approach with data collection techniques using a questionnaire. The number of research samples was 51 students, consisting of 2019 Building Engineering Education students. Based on the results of the data analysis that has been carried out, it shows that the emotional intelligence and work readiness of Building Engineering Education students Universitas Pendidikan Indonesia are in the fairly high category, and there is a significant influence of emotional intelligence on work readiness of Indonesian Education University Building Engineering students.